Investigations of the static and dynamic performances of an annular seal with a tilted rotor by transient CFD methods with dynamic mesh - Li, Fengqin; Zhai, Lulu; Cui, Baoling; Zhu, Zuchao; Guo, Jia (Frontiers in Energy Research, 2022)
The rotor is tilted in an annular seal, due to impeller radial load and the installation error of various components, which has great influences on the vibration and stability of pump systems. In this paper, a transient computational fluid dynamics (CFD) method is applied to study the static and dynamic performances of an annular seal with a tilted rotor. Then, the effects of seal length, static misalignment angle, misalignment mode, pressure difference and rotational speed on the static and dynamic performances of the annular seal are also investigated by the method. The results shows that when length-diameter (L/D) ratio is more than 1, stiffness coefficients and damping coefficients under different rotational speeds of the three pressure differences increase as L/D ratio increases. A large L/D ratio will impair the dynamic stability of the tilted annular seal, but it can effectively reduce leakage flowrate. Besides, for the misalignment mode where the rotor axis passes through the middle plane of the annular seal, direct stiffness coefficient increases with the misalignment angle, while the other coefficients are insensitive to the angle. For the misalignment modes where the rotor axis passes through the seal entrance plane and the seal quarter plane, all dynamic coefficients increase with the increasing angle, except for cross-coupled damping coefficients, which decrease with the increasing angle.